Women's Iddah Period in 'Grey Divorce': Reformulation of Islamic Marriage Law in Indonesia Based on Maqāṣid al-Sharī‘ah - Hardani, Sofia; Erman, Erman; Bratasena, Iqbal Prima (El-Usrah: Jurnal Hukum Keluarga, 2026)
Marriage, divorce, maintenance, inheritance, and the legal consequences arising from these issues are problematic issues in Islamic family law that will always arise in Muslim communities in Indonesia and throughout the Muslim world. The phenomenon of 'divorce at an advanced age' (divorce among the elderly) is increasing in Indonesia, triggering normative challenges in Islamic marriage law, especially regarding the mandatory iddah period for menopausal women. The study uses empirical legal methods, explained by the theory of maqāṣid al-sharī‘ah. Data were collected through interviews and literature studies. The literature reviewed includes classic legal texts such as fiqh books, journal articles, and legislation. This study concludes that, based on the Compilation of Islamic Law, Article 153 paragraph (6) of the Indonesian Islamic Law Code (KUHP), an iddah period of one year is mandatory for menopausal women. This period is much longer if we use the Georgian Calendar and raises critical questions in the context of 'divorce at an advanced age', where the main purpose of iddah—istibra al-rahim (ensuring an empty uterus) is medically irrelevant. This study reveals that the classical provisions on 'iddah menopause are ijtihadi (dependent on legal reasoning) and contextual, so they are open to normative reformulation. Consequently, this article proposes a reformulation of Article 153 (6) of the KHI to be more gender-just and responsive to maqāṣid. By distinguishing between ’iddah ta'abbudi (ritualistic) and ’iddah ta'aqquli (rational) in the context of ‘grey divorce’, this reformulation aims to strengthen legal protection for women while maintaining the relevance of Islamic family law in Indonesia.